Qualitative research design: Flexibility and specificity - Delliou, Foudil (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
Traditionally, works on research design in social sciences focus on quantitative research. It have understood “design” as a strategy that predetermines all the steps of any research project. Given that qualitative research is considered as an interpretative and interactive approach to study topics in their natural context, trying to understand and interpret the phenomenon according to the meanings given to it by the informants, it can be understood that qualitative research does not use any prior design. This paper aims to emphasize the importance of the research design process of both quantitative and qualitative research, because the design is subject to the nature of the research topic and how to approach it and not vice versa. In other words, the design can be used in all types of research because of its ability to adapt to its specific requirements. In qualitative research, design is very important because it reflects the conception of applied research procedures that are “flexible” and almost “specific” to each type of qualitative research. Therefore, it differs from the design of quantitative research that usually uses pre-established applied research procedures. This article also aims to reflect that into standard, special qualitative design models (grounded, ethnographic, narrative, interactive, analytical-qualitative...) and mixed ones (quantitative-qualitative or vice versa), and this after a conceptual introduction to qualitative research that highlights its interpretive and interactive characteristics and inductive logic and exposes its types, each of which is distinguished by its own design, despite having in common some main steps.